Continuous-flow photocatalytic reduction of chromium (VI) using titanium dioxide supported on a cellulosic material: Effects of operational parameters and scavenger study - Sana Esserrar; Anas Salhi; Mohammed El Amine Ghanjaoui; Mohammed El Krati; Soufiane Tahiri (Next Materials, 2025)
Separating suspended titanium dioxide (TiO2) from the reaction medium presents a considerable challenge in conventional photocatalysis, often resulting in higher treatment costs. However, employing TiO2 immobilized on a support can effectively mitigate this problem. This study aims to use a catalytic sheet containing TiO2 for reducing hexavalent chromium (Cr(VI)) in aqueous solutions circulating within a photo-reactor. Continuous flow systems are easier to scale up for industrial applications, allowing for larger volumes of treatment or production. The impacts of pH, irradiation duration, concentration of chromium, treatment volume, feed flow rate, and the presence of inorganic salts and scavengers were evaluated. The reduction process reaches its maximum at pH 2 and can significantly be enhanced when hole scavengers such as ethanol, citric acid, oxalic acid, and hydrogen peroxide are added to reaction medium. In contrast, chloroform and inorganic salts exhibit inhibitory effects on the process. The reduction mechanism relies on superoxide radicals (•O2-) and electrons (e-) on TiO2 conduction band (CB). Moreover, the findings suggested that the catalytic material demonstrated outstanding reusability and stability across multiple cycles.